PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN KOMIK UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Mahmudah, Muhlisatul; MT, A. Mujib; Fauzen, Muhammad Anis (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
This study aims to improve the learning interest in mathematics of seventh-grade students at SMP Islam Plus Miftahul Warisin through the implementation of a comic-assisted Problem Based Learning (PBL) model. The initial problem identified was the low level of students’ learning interest, indicated by a lack of active participation, feelings of boredom during lessons, and difficulties in performing mathematical calculations. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 20 seventh-grade students. Data collection techniques included observation, learning interest questionnaires, and documentation. The results showed a gradual improvement in students’ learning interest after the implementation of the comic-assisted PBL model. The number of students categorized as having low learning interest decreased from 15 students in the pre-cycle stage to 9 students in Cycle II, while the number of students in the interested and moderately interested categories increased. Therefore, the application of the comic-assisted Problem Based Learning model proved effective in enhancing students’ learning interest in mathematics learning. ABSTRAK Penelitian ini bertujuan untuk meningkatkan minat belajar matematika siswa kelas VII SMP Islam Plus Miftahul Warisin melalui penerapan model pembelajaran Problem Based Learning (PBL) berbantuan media komik. Permasalahan awal yang ditemukan adalah rendahnya minat belajar siswa yang ditandai dengan kurangnya keaktifan, rasa bosan dalam pembelajaran, serta kesulitan siswa dalam melakukan perhitungan matematika. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, masing-masing terdiri atas tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian berjumlah 20 siswa kelas VII. Teknik pengumpulan data meliputi observasi, angket minat belajar, dan dokumentasi. Hasil penelitian menunjukkan adanya peningkatan minat belajar siswa setelah penerapan model PBL berbantuan komik. Jumlah siswa yang berada pada kategori kurang berminat mengalami penurunan dari 15 siswa pada pra-siklus menjadi 9 siswa pada siklus II, sedangkan jumlah siswa yang berminat dan cukup berminat mengalami peningkatan. Dengan demikian, penerapan model Problem Based Learning berbantuan komik efektif dalam meningkatkan minat belajar siswa pada pembelajaran matematika.